Factors Affecting the Development of Small Medium Enterprises in the Niger Republic: An Exploratory Study - Hamidou Taffa Abdoul-Azize (Cita Konsultindo Research Center, 2022)
Over the past few years, the Republic of Niger has seen an increase in young entrepreneurs across a wide range of sectors. Many obstacles could impede the progress of these entrepreneurs. This study examines the factors that affect the development of small-medium enterprises in the Niger Republic. Based on primary data collected from entrepreneurs, factor analysis was performed. The findings of the study showed that the most significant factors of the development of small-medium enterprises in the Niger Republic were the